2009
DOI: 10.1111/j.1440-1770.2009.00391.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial processes at the land–water interface, and cross‐domain causal relationships, as influenced by atmospheric deposition of pollutants in three freshwater lakes in India

Abstract: The effects of long-term atmospheric deposition of pollutant elements on the trans-surface causative relationships at three lake sites having different catchment characteristics were investigated in this study. The selected determinants included lake productivity, bottom sediment quality, and a suite of microbial variables (microbial biomass (C mic ); basal respiration; substrate-induced respiration; bacterial:fungal ratio; metabolic quotient; and alkaline phosphatase and FDAase activities) measured at the lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…The potassium exhibits negative correlation with sulfate. The concentration of phosphate in harvested rainwater was similar to those reported at some other locations of India (Das et al, 2005;Pandey and Pandey, 2009). The maximum permissible limit of phosphate in drinking water 6 ppm, ADB proposed water quality standard for Bangladesh (ADB, 1994).…”
Section: CL Hco 3 Po 4 So 4 and Nosupporting
confidence: 86%
“…The potassium exhibits negative correlation with sulfate. The concentration of phosphate in harvested rainwater was similar to those reported at some other locations of India (Das et al, 2005;Pandey and Pandey, 2009). The maximum permissible limit of phosphate in drinking water 6 ppm, ADB proposed water quality standard for Bangladesh (ADB, 1994).…”
Section: CL Hco 3 Po 4 So 4 and Nosupporting
confidence: 86%
“…Atmospheric deposition, clearfall and run-off waters were analyzed for SO 4 2-, NO 3 -, NH 4 ? and PO 4 3-as described by Pandey and Pandey (2009) and Na ? , K ?…”
Section: Methodsmentioning
confidence: 99%
“…Role of such trans-boundary linked changes becomes important in areas characterized by unprecedented increase in atmospheric deposition. Studies have indicated atmospheric deposition of reactive N as high as 20 to 60 kg ha 1 yr 1 in many ecosystems of Europe (Bobbink and Lamers, 2002) and 12 to 46 kg ha 1 yr 1 in many parts of India (Pandey and Pandey, 2009;Pandey et al, 2014). Nitrate concentrations in Norwegian lakes doubled in less than a decade due to air-driven deposition (Vitousek et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Significant correlations (R 2 0.9735 0.9764; P 0.001) between AD-nutrients and microbial activity indicated the influence of AD-nutrients on microbial processes in lake catchment. It is possible that AD-nutrients improve the poor substrate quality of OM to enhance microbial colonization (Wedin and Tilman, 1996;Elser et al, 2000;Pandey and Pandey, 2009). …”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation